The SAFE Pilot Trial—SAlvage Focal Irreversible Electroporation—For Recurrent Localized Prostate Cancer: Rationale and Study Protocol - Marra, Giancarlo; Shah, Taimur T.; D’Agate, Daniele; Marquis, Alessandro; Calleris, Giorgio; Lunelli, Luca; Filippini, Claudia; Oderda, Marco; Gatti, Marco; Valerio, Massimo; Sanchez-Salas, Rafael; Bossi, Alberto; et al. (Frontiers in Surgery, 2022)
Abstract Background: Currently, the majority of prostate cancer (PCa) recurrences after non-surgical first line treatment are managed with androgen-deprivation therapy (ADT). Salvage radical prostatectomy (sRP) is a curative alternative to ADT but yields significant morbidity. Preliminary evidence from focal salvage treatments shows similar oncological control but lower morbidity compared to sRP. Amongst available ablative focal energies Irreversible Electroporation (IRE) is a treatment modality which proved promising, especially in treating apical lesions, where PCa most often recurs. Our aim is to test the safety of salvage IRE for recurrent PCa. Methods: We will perform a single-arm pilot feasibility study (IDEAL stage 2a): SAFE, SAlvage Focal irreversible Electroporation for recurrent localized PCa. Twenty patients with biopsy-proven PCa recurrence after primary non-surgical (radiation or ablation) treatment will be included. All men will undergo mpMRI +/- targeted biopsies, pre-operative PSMA-PET staging before inclusion and sIRE. Outcomes will be evaluated through internationally validated questionnaires and morbidity scales. All men will undergo a control biopsy at one year. Results: Primary Objectives: Evaluation of safety of sIRE (and patients’ quality of life) after treatment. Secondary Objectives: Evaluation of functional outcomes, namely continence and erectile function changes and evaluation of short-term oncological efficacy. Conclusions: SAFE will be the second pilot study to evaluate sIRE and the first one performed according to the most recent diagnostic and staging imaging standards. sIRE may provide a curative option for recurrent PCa together with lower comorbidities compared to sRP.